2018
DOI: 10.1073/pnas.1722317115
|View full text |Cite
|
Sign up to set email alerts
|

Targeting β1-integrin inhibits vascular leakage in endotoxemia

Abstract: SignificanceCompromised vascular integrity is associated with capillary leakage in sepsis, but effective therapies stabilizing the vasculature are lacking. Here, we show that targeting β1-integrin in vivo with inhibitory antibodies or deletion of a single allele of endothelial β1-integrin inhibits lipopolysaccharide (LPS)-induced vascular leakage in murine endotoxemia. The inflammatory agents IL-1β, thrombin, and LPS induced changes in endothelial cell–extracellular matrix (ECM) adhesion via β1-integrin, angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 34 publications
10
82
0
Order By: Relevance
“…Prior to FBSR, our confocal-based TFM analyses have yielded between 0.2 to 0.5 trackable beads per square micrometre (Jacquemet et al, 2019;Närvä et al, 2017;Georgiadou et al, 2017;Hakanpaa et al, 2018) (Figure 1f), in agreement with values reported by others (Colin-York et al, 2016). Here, by implementing FBSR, and conservative reconstruction parameters, we were able to substantially increase the number of trackable beads to 1.2 beads per square micrometre ( Figure 1f).…”
Section: Increasing the Bead Density Of Tfm Gels Using Fluctuationbassupporting
confidence: 86%
See 1 more Smart Citation
“…Prior to FBSR, our confocal-based TFM analyses have yielded between 0.2 to 0.5 trackable beads per square micrometre (Jacquemet et al, 2019;Närvä et al, 2017;Georgiadou et al, 2017;Hakanpaa et al, 2018) (Figure 1f), in agreement with values reported by others (Colin-York et al, 2016). Here, by implementing FBSR, and conservative reconstruction parameters, we were able to substantially increase the number of trackable beads to 1.2 beads per square micrometre ( Figure 1f).…”
Section: Increasing the Bead Density Of Tfm Gels Using Fluctuationbassupporting
confidence: 86%
“…Next, we sought to demonstrate that our improved TFM pipeline could be used to answer biologically relevant questions. In particular, TFM is very commonly used to assess how a protein or a drug treatment influences the ability of cells to exert forces on their environment (Jacquemet et al, 2019;Hakanpaa et al, 2018;Närvä et al, 2017). For this purpose, we aimed to cause a mild perturbation to simulate a plausible biological response and treated cells with either DMSO or the myosin II inhibitor blebbistatin for 15 minutes (Figure 4a and 4b).…”
Section: Biologically Relevant Applications Of Fluctuation-based Tfmmentioning
confidence: 99%
“…Intriguingly, work by Hakanpaa et al showed that the deletion of a single β1 integrin allele in ECs of established blood vessels did not alter basal permeability but rather protected β1 EC heterozygous mice from LPS-induced hyperpermeability compared to wild type littermates. 67 Furthermore, pharmacological inhibition of β1 integrin also mitigated LPS-induced tracheal permeability. Prior to LPS treatment, wildtype mice were prophylactically administered either a β1 blocking antibody (HMβ1-1) or an isotype nonimmune IgG control with the former group showing reduced levels of FITC-dextran extravasation relative to control.…”
Section: Role Of β1 Integrins In Ec Barrier Functionmentioning
confidence: 98%
“…Prior to LPS treatment, wildtype mice were prophylactically administered either a β1 blocking antibody (HMβ1-1) or an isotype nonimmune IgG control with the former group showing reduced levels of FITC-dextran extravasation relative to control. 67 It was therefore proposed that in quiescent endothelium β1 integrin predominantly localizes to FAs whereas inflammatory molecules acting in an angiopoietin-2-dependent manner induce β1 integrin association with tensin at fibrillar adhesions. β1 integrin-positive fibrillar adhesions in turn promote cytoskeletal tension that alters cell-cell junctions and increases vascular permeability.…”
Section: Role Of β1 Integrins In Ec Barrier Functionmentioning
confidence: 99%
“…Integrins are involved in a vast spectrum of biological processes, including cell adhesion, gene expression, proliferation, and cell migration 40 . Deletion of fibronectin or fibronectin-binding integrins (α5β1, αvβ3) limits endothelial NF-κB activation and proinflammatory gene expression in atherosclerosis models 9,11 , whereas β1 integrin inhibition reduces vascular permeability in response to proinflammatory mediators (LPS, IL-1β) 41 . To dissect the role of integrin signaling in endothelial cell phenotype, several groups have used variety of integrin inhibitors and blocking antibodies to implicate integrin activation and new integrin-matrix interactions in endothelial proinflammatory responses, particularly in response to flow and oxLDL 8,12 .…”
Section: Discussionmentioning
confidence: 99%